An unexpected source of invertebrate community recovery in intermittent streams from a humid continental climate. (13th August 2019) - Pařil, Petr; Polášek, Marek; Loskotová, Barbora; Straka, Michal; Crabot, Julie; Datry, Thibault
Abstract: Intermittent streams are naturally dominant landscape features of Mediterranean and arid regions, but also occur more and more in humid climates, such as in the Czech Republic. Organism abilities to cope with drying (i.e. resistance forms) have been quantified in naturally intermittent streams from Mediterranean and arid regions, in which long‐term flow intermittence patterns have promoted physiological adaptations. In contrast, the capacity of aquatic communities to persist without requiring resistance adaptations under recent intermittent flow regimes in more humid climates is virtually unexplored, along with its contribution to community recovery upon rewetting. Here, we addressed the ability of aquatic invertebrates devoid of specific desiccation‐resistance forms (e.g. cysts or eggs) to cope with climate change‐induced flow intermittence from rivers in continental climate. Owing to the high relative air humidity, the importance of riparian cover and the short duration of drying events, we expected taxonomically and functionally rich communities to persist in the dry streambed during phases with no surface water and to contribute to community recovery upon flow resumption. To explore these ideas, we collected invertebrate communities in the riverbeds before, during and after drying from 10 intermittent rivers in the Czech Republic. We quantified the pool of organisms remaining alive in the dry riverbeds and determined its taxonomic and functional contribution to the recovery of benthic communities upon rewetting. Of the organisms collected, 83%, belonging to 22 taxa, were able to survive during the dry phase without producing desiccation‐resistance forms. This pool of organisms contributed substantially both taxonomically and functionally to the quick recovery of benthic communities. The exponential decrease in taxonomic and functional richness implies an initial quick loss of sensitive taxa, while a pool of less sensitive taxa persisted long in the dry riverbeds, hence contributing to the fast community recovery upon rewetting. Survival rates of active aquatic macroinvertebrates devoid of specific desiccation‐resistance adaptations have rarely been quantified. Probably promoted by benign environmental conditions prevailing on dry riverbeds in this study, their survival demonstrated the need to protect communities in dry riverbed and their adjacent riparian environments so that assemblages can recover rapidly from short periods without river flow. Riparian forest management along intermittent streams from continental climates could help conserve the value of dry streambeds as a source of resilience for riverine communities.